Linear shrinkage, strength and porosity of alumina-based ceramic foam with corn starch as pore former - Abdul Rahman, Nurul Farhana; Abd.Rahman, Hamimah; Wan Azhan, Wan Muhammad Syahmi; Yatim, Nor Hamidah (Trans Tech Publications, 2021)
In this study, ceramic foams were produced using starch consolidation casting method. This research focused on the preparation of alumina-based ceramic foam by using corn starch as a pore-forming agent. Preparation of alumina based ceramic foam is studied to observe the effect of the addition of corn starch on its physical, mechanical and morphological properties. The composition of the suspension used included 58-64 wt.% alumina, 55 wt.% deionised water and other materials, such as silica and polyethylene glycol (PEG), were used as additive and dispersing agent respectively. The ceramic foam gave a linear shrinkage from 1.07% to 3.39%. The obtained flexural strength was between 0.594 and 1.996 MPa. The average total porosity ranged from 54.05% to 70.70%. This study found that the suitable amount of corn starch in alumina foam is 4 wt.% because the resulting porosity values and flexural strength are appropriate for ceramic foams.